Carnival Story Based on a Story by Marcy Klauber and Charles Williams - Neumann, Kurt; Haller, Ernest; Baxter, Anne; Cochran, Steve; Bettger, Lyle (VCI Entertainment, 2020)
The classic story of an ambitious German girl (Anne Baxter) who joins a traveling carnival and eventually becomes a high-wire superstar. A dramatic love triangle follows when she unknowingly captures the hearts of two circus performers who vie for her attention. [www.vcientertainment.com]